Examining Risk Factors Accelerating Time-to-Chronic Obstructive Pulmonary Disease (COPD) Diagnosis among Asthma Patients. Issue 1 (31st December 2022) - Asamoah-Boaheng, Michael; Farrell, Jamie; Osei Bonsu, Kwadwo; Midodzi, William K.
Abstract: Asthma patients may have an increased risk for diagnosis of chronic obstructive pulmonary disease (COPD). However, risk factors accelerating time-to-COPD diagnosis are unclear. This study aims to estimate risk factors associated with the incidence of COPD diagnosis in asthma patients. Canada's Population Data BC (PopData BC) was used to identify asthma patients without prior COPD diagnosis between January 1, 1998, to December 31, 1999. Patients were assessed for time-to-incidence of COPD diagnosis from January 1, 2000, to December 31, 2018. The study estimated the effects of several risk factors in predicting the incidence of COPD in asthma patients during the 18-year follow-up period. Patient factors such as Medication Adherence (MA) were assessed by the proportion of days covered (PDC) and the medication possession ratio (MPR). The log-logistic mixed-effects accelerated failure time model was used to estimate the adjusted failure time ratios (aFTR) and 95% Confidence Interval (95% CI) for factors predicting time-to-COPD diagnosis among asthma patients. We identified 68, 211 asthma patients with a mean age of 48.2 years included in the analysis. Risk factors accelerating time-to-COPD diagnosis included: male sex (aFTR: 0.62, 95% CI:0.56–0.68), older adults (age > 40 years) [aFTR: 0.03, 95% CI: 0.02–0.04], history of tobacco smoking (aFTR: 0.29, 95% CI: 0.13–0.68), asthma exacerbations (aFTR: 0.81, 95%CI: 0.70, 0.94), frequent emergency admissions (aFTR:0.21, 95% CI: 0.17–0.25), longer hospital stay (aFTR:0.07, 95% CI: 0.06–0.09), patients with increased burden of comorbidities (aFTR:0.28, 95% CI: 0.22–0.34), obese male sex (aFTR:0.38, 95% CI: 0.15–0.99), SABA overuse (aFTR: 0.61, 95% CI: 0.44–0.84), moderate (aFTR:0.23, 95% CI: 0.21–0.26), and severe asthma (aFTR:0.10, 95% CI: 0.08–0.12). After adjustment, MA ≥0.80 was significantly associated with 83% delayed time-to-COPD diagnosis [i.e. aFTR =1.83, 95%CI: 1.54–2.17 for PDC]. However, asthma severity significantly modifies the effect of MA independent of tobacco smoking history. The targeted intervention aimed to mitigate early diagnosis of COPD may prioritize enhancing medication adherence among asthma patients to prevent frequent exacerbation during follow-up.